Optimalisasi Tata Kelola SDM dalam Penyediaan Layanan Publik di Desa Gembongan - Izzatus Syifa, Afida; Muhaimin, Hikmah; Ratna Rinayuhani, Tri (MAJAPAHIT POLICY, 2024)
This study aims to analyze the optimization of human resource governance in the provision of public services in Gembongan Village, Gedeg District, Mojokerto Regency, using a qualitative approach through observation, interviews, and documentation. Primary data were obtained from interviews with village officials and local communities, while secondary data came from journals and relevant documents. The results of the study indicate that the recruitment process for village officials is in accordance with regulations, and training organized by the district government focuses on increasing the capacity of officials, especially in technology-based financial management. Performance assessments are carried out by the Village Consultative Body (BPD) with indicators of attendance, participation, and quality of service. However, there are several obstacles in optimizing human resource governance, such as low motivation, work ethic, and differences in technological capabilities. These obstacles hinder adaptation to technological changes and the implementation of public services, including night services, which have not been running optimally. This study emphasizes the importance of ongoing training and technical support to improve the quality of public services that are appropriate according to applicable provisions, so that the community can feel the maximum benefits.